PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN PADA TOKO ROTI DAN OLEH-OLEH KHAS SIAK DAPUR MAMA NIZAM SIAK SRI INDRAPURA - Meissy Febiyola Putri; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Consumer satisfaction is one of the most important factors in the marketing concept, this is the background of this research. Good service quality, appropriate pricing is the most important part of supporting factors for customer satisfaction. This study aims to determine service quality, pricing, and customer satisfaction at the Siak Kitchen Mama Nizam Siak Sri Indrapura Bakery and Souvenirs Shop, to determine the effect of service quality on customer satisfaction at the Mama Nizam Bakery and Typical Souvenir Shop. Siak Sri Indrapura, to determine the effect of pricing on consumer satisfaction at the Siak Kitchen Mama Nizam Bakery and Souvenir Shop and to determine the effect of service quality and pricing on customer satisfaction at the Siak Kitchen Mama Bakery and Typical Souvenirs. Nizam Siak Sri Indrapura. The research location is in the Siak Kitchen Bakery and Souvenirs Typical Kitchen Mama Nizam Siak Sri Indrapura on Jalan Raja Kecik, Kampung Dalam Village, Siak District, Siak Sri Indrapura Regency. The research sample was 100 respondents with accidental sampling technique. The research method used is descriptive quantitative analysis, the sample with data sources from primary data and secondary data. The analytical method used in this research is simple linear regression analysis, multiple linear regression, and through validity and reliability tests. In this study the results obtained are that Service Quality (X1) has an effect on Consumer Satisfaction (Y), Pricing has an effect on Consumer Satisfaction (Y), and Service Quality (X1) and Price Fixing (X2) has an effect on Consumer Satisfaction (Y) at the Bakery and Souvenirs Typical Siak Kitchen Mama Nizam Siak Sri Indrapura. Keywords: Service Quality, Pricing, Consumer Satisfaction